Digital Literacy and Entrepreneurial Attitudes: A Study of Indonesian University Students - Joni Iskandar; Sukriyah; Gusli Chidir; Jainuri; Yosua Novembrianto Simorangkir (International Journal of Management and Economic Research (IJOMER), 2024)
Technological advancements have created many opportunities for young entrepreneurs to develop and expand their business operations. Therefore, the internet has encouraged the emergence of digital entrepreneurship as a growing form of entrepreneurship among many young entrepreneurs and even university students, who are indeed the digital native generation. This study examines the extent to which the personal characteristics of digital natives among university students in Indonesia impact their digital entrepreneurship intention. This study examines the direct impact of five personal traits adopted from the big five personal traits, namely openness to experience, conscientiousness, extraversion, agreeableness, and neuroticism, on personal attitude and digital entrepreneurship intention. For this purpose, the respondents were 254 Indonesian university students using simple random sampling technique. Structural equation modelling using SEM SmartPLS 4.0. The results of this study reveal that all hypotheses are proven to have a significant positive effect, namely the five personal characteristics of college students (agreeableness, conscientiousness, extraversion, neuroticism, and openness to experience) have a positive effect on personal attitude. Furthermore, the attitude variable also has a positive effect on digital entrepreneurship intention. The results of this study contribute to the research gap on the big five personal traits, personal attitude and digital entrepreneurship intention. Theoretical and practical implications have been discussed and become important recommendations for the future projections of students, teaching lecturers, and also for management policies in higher education.